Prevalence of overweight and obesity among 7-9 year-old children in Aveiro, Portugal: Comparison between IOTF and CDC references - Pedrosa, Carla (2011)
Objective: To estimate the prevalence of overweight and obesity in schoolchildren from Aveiro, Portugal, according to two criteria: the International Obesity Task Force (IOTF) and the US Centers for Disease Control and Prevention (CDC) cut-offs. Design: Weight, height and waist circumference were measured. Using the BMI, gender- and age-specific prevalences of overweight and obesity were determined according to the IOTF cut-offs extrapolated from an adult BMI of 25 and 30 kg/m(2) and the CDC cut-off values of 85th and 95th BMI percentile. Setting: Aveiro, Portugal. Subjects: A random representative sample of 905 children (457 boys; 448 girls) aged 7-9 years. Results: The prevalence of excess weight (overweight and obesity) was lowest according to IOTF cut-offs compared to CDC (28.1% v. 31.2%), especially obesity (8.1% v. 14.0%). However, the CDC and IOTF criteria have a strong agreement (Cohen's k=0.755; P<0.001). There were significant differences in excess weight between boys and girls according to the CDC (26.9% v. 35.7%; P=0.003). Obese children are younger and the majority present abdominal obesity. Conclusions: The present study shows a high prevalence of excess weight in Aveiro children, similar to other Portuguese regions and among the highest in Europe, especially in the female gender. The IOTF cut-off values give a lower prevalence of excess weight, namely obesity.